The Political-Social Ideology of the Workers in the Hoja Obrera, 1909-1912 - Angulo Brenes, Sonia (2023)
The article rebuilds the socio-political ideology of workers, men and women, from one of the most important worker publications for the period studied: the Hoja Obrera Journal. Workers’ ideas from this period are identified and analyzed; they are related to social inequality, the worker organization and union, politics, homeland and patriotism, the establishment of a work party, and its definition of workers. Through a methodology based on the study of the Hoja Obrera publications between 1909 and 1912, it concludes the diversity of ideas about these topics and the syncretism of their political influences, among them liberalism, socialism, and anarchism, just as its critical look before conceptions like the homeland and patriotism.